The Stunning Glamour Scarf / Halimatun Saadiah Saad and Siti Athirah Hannah Ibrahim - Saad, Halimatun Saadiah; Ibrahim, Siti Athirah Hannah (2022)
The Stunning Glamor Scarf sells various types of scarves that have various colors and patterns that gives high satisfaction on consumers. Most importantly all the materials we sell are high quality and cool when worn. The product that The Stunning Glamor Scarf offers is Bawal Cotton, Soraya Cotton Curve, Elena, Cotton Shawl, Sulam Shawl Kencana and others. For our company, The Stunning Glamor Scarf has a slogan that is "A Woman In A Hijab Is Like A Pearl In Its Shell" it symbolizes to our beloved customers. The major purpose for the company is to give a high-quality hijab with a diversity of patterns with inexpensive and acceptable rates with elegant appearance ready to wear on our consumers. On April 12, 2022, we launched our internet company utilizing a Facebook Page-based social media platform. Our intended consumers are students as we are next to campus. In addition, we also target all ladies out there, teenage girls and adults. We also make many promotions, especially on celebration days such as Raya Aidilfitri, Raya Aidiladha, etc. Price offered at The Stunning Glamor Scarf very cheap and worth it.